SINKRONISASI DAN DIFERENSIASI PUTUSAN HAKIM DALAM PENYELESAIAN KASUS-KASUS KEKERASAN DALAM RUMAH TANGGA - Tjokorda Istri Putra Astiti (University of Udayana, 2014)
This study specifically aims to assess synchronization and differentiation between the judge's decision, both horizontally and vertically, especially with regard todomestic violence cases. In addition, this study also intends to study about rule whichare applied by the Judges on the cases, and reveal whether the decision under reviewreflects the gender justice This research is a legal normative research using case approach which wasexamined by studying the Judge’s decision in concrete cases, especially with regard todomestic violence. The number of decisions that were examined are six decisions whichconsists of three decisions of the District Court (Pengadilan Negeri) and threedecisions of the High Court (Pengadilan Tinggi). The decisions are determined bypurposive sampling. Based on the analysis of the six decisions mentioned above , can be concludedas following:1) The rule applied by the judge in hanling the concrete cases regarding domestic violence particularly violence against women is on the Domestic Violence Act ( ActNo. 23/2004 ) with the application of a kind of sanction of imprisonment rangingfrom 1-3 months, that varied there the defendant was arrested some are droppedwith conditional (pidana bersyarat) (not being held prisoner) 2) Among the three decisions of the District Court and the three decitions of the HighCourt which have analysed, in one hand show synchronization and the other hand show differentiation. In this case, synchronization and differentiation can be seen vertically (between the District Court and the High Court decision), andhorizontally (between the District Court to each other) or between the decision ofthe High Court to each other). 3) That the decision of the District and the High Court, either have reflected gendersensitively and gender equity.